Konsentrasi Efektif Ekstrak Daun Salam (Syzygium polyanthum Wight) terhadap Hambatan Biofilm Enterococcus faecalis (Effective Concentration of Bay Leaf Extract (Syzygium polyanthum Wight) to Inhibit Enterococcus faecalis Biofilm) - Shufiyah Nurul Aini; Ruslan Effendy; Ira Widjiastuti (Conservative Dentistry Journal, 2016)
Background. Enterococcus faecalis is the most dominant microorganisms found in endodontic secondary infection with prevalence ranging between 24% - 77%. Defense mechanism of Enterococcus faecalis bacteria is forming biofilm,. A study showed that bacteria in mature biofilms can 10-1000 times more resistant to antimicrobials than bacteria in a planktonic form. One of the natural substances that can be used as antibiofilm to irrigation root canals is extract of fresh bay leaf (Syzygium polyanthum Wight). Chemical components in bay leaves include flavonoids, tannins, and essential oils, which have antibacterial capability and damage the membrane biofilm. Purpose. To determine the effective concentration of fresh bay leaf extract (Syzygium polyanthum Wight) that can inhibit biofilm Enterococcus faecalis. Method. This research is in-vitro labolatory experimental with post test only control group design using microtitter plate assay. Samples using Enterococcus faecalis ATCC 29212 cultured in TSB (Trypticase Soy Broth) + glucose.Bay leaf extract (Syzygium polyanthum Wight) concentration in this study was 13%, 12.25%, 11.50%, 10.75%, 10%, 9.25%, 8.50%, 7.75%, 7%, and 6.25%. Results. At the 13% concentration of Syzygium polyanthum Wight, showed 100% inhibition of biofilm, means that the 13% concentration of bay leaf extract (Syzygium polyanthum Wight) can totally inhibit biofilm formation of Enterococcus faecalis. Conclusion. The effective concentration of bay leaf extract (Syzygium polyanthum Wight) which inhibit Enterococcus faecalis biofilm is 13%.